2017
DOI: 10.3892/ol.2017.6885
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of tumor lymphangiogenesis and lymphatic vessel density in endometrioid carcinoma of the uterine corpus

Abstract: The present study aimed to assess the prognostic significance of tumor lymphangiogenesis and lymphatic vessel density (LVD) in endometrioid carcinoma of the uterine corpus. The association between LVD and various factors, including lymphatic vessel invasion (LVI), and nodal metastases, were investigated. Among 202 surgically treated cases, 19 cases with nodal metastases with the infiltration reaching the outer-half myometrium (N+ group) were selected. The LVDs of hotspots in each case were examined at 100× mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It was reported that poor outcome is correlated with lymphovascular invasion ( 8 ), aggressive histology and cervical invasion in early (stage I or II) EMC in the multivariate analysis ( 1 ). In addition, elderly EMC patients (≥70 years) appear to have worse outcomes compared with younger patients, regardless of other poor prognostic factors, and EMC also appears to be intrinsically more aggressive in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that poor outcome is correlated with lymphovascular invasion ( 8 ), aggressive histology and cervical invasion in early (stage I or II) EMC in the multivariate analysis ( 1 ). In addition, elderly EMC patients (≥70 years) appear to have worse outcomes compared with younger patients, regardless of other poor prognostic factors, and EMC also appears to be intrinsically more aggressive in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of patients with EMC is associated with variable pathological factors, including histological type, tumor grade ( 7 ), depth of myometrial invasion and lymphovascular invasion ( 8 ), as well as clinicopathological stage as determined by the International Federation of Gynecology and Obstetrics (FIGO) classification ( 9 ), which is a critical determinant of the prognosis of EMC, irrespective of its histological type. Tumor grade is essentially prognostic for endometrioid carcinoma, but not for type II EMC, as this type has the potential to behave aggressively ( 10 ).…”
Section: Introductionmentioning
confidence: 99%